Loopster: Static loop termination analysis - XIE, Xiaofei (Institutional Knowledge at Singapore Management University, 2017)
Loop termination is an important problem for proving the correctness of a system and ensuring that the system always reacts. Existing loop termination analysis techniques mainly depend on the synthesis of ranking functions, which is often expensive. In this paper, we present a novel approach, named Loopster, which performs an efficient static analysis to decide the termination for loops based on path termination analysis and path dependency reasoning. Loopster adopts a divide-and-conquer approach: (1) we extract individual paths from a target multi-path loop and analyze the termination of each path, (2) analyze the dependencies between each two paths, and then (3) determine the overall termination of the target loop based on the relations among paths. We evaluate Loopster by applying it on the loop termination competition benchmark and three real-world projects. The results show that Loopster is effective in a majority of loops with better accuracy and 20 \texttimes{}+ performance improvement compared to the state-of-the-art tools.